Molecular Characterization of Clinical Isolates of Enteropathogenic Escherichia Coli from Miri Sarawak - Lah, Irene (2004)
A total of thirty two strains of clinical enteropathogenic Escherichia coli (EPEC) isolated from Hospital Miri, Sarawak were examined and further characterized by various molecular techniques. These techniques include the plasmid profiling, antimicrobial resistance, resistance and virulence genes detection by multiplex PCR, RAPD, ERIC and PFGE genomic fingerprinting. All the strains studied were found to exhibit multiple antibiotics resistance patterns to twelve antibiotics [penicillin (100%), teicoplanin (100%), vancomycin (100%), bacitrasin (97%), methicillin (97%), erythromycin (69%), ampicillin (63%), cephalothin (47%), streptomycin (25%), chloramphenicol (16%), kanamycin (6%) and nalidixic acid (3%)] used. Thirteen EPEC isolates were shown to encode ampicillin resistance by means of the blaTEM gene respectively, and none of the EPEC isolates showed the presence of the sipB/C, cmlA/tetR and blaPSE-1 genes. The plasmid profiles obtained ranged in size from 1.8 MDa to 57 MDa. Two types of specific primer encoding the Shiga-like Toxin gene, the SLTII (584 bp) gene and SLTI (348 bp) were utilized in the multiplex PCR assay. Analysis carried out demonstrated that all were positive for the presence of the SLTII and SLTI gene. Two EPEC isolates analysed by PCR were confirmed to be the O157:H7 serogroup as determined by agglutination tests with specific antisera. Three 50% G+C contents 10-mer random primers, the Gen 1-50-02 (5’- CCAAACTGCT-3’), Gen 1-50-08 (5’-GAGATGACGA-3’), and Gen1-50-09 (5’- TCGCTATCTC-3’) were chosen after screening through ten random primers. In PFGE technique carried out, two kinds of restriction enzymes, the SpeI (5’-A CTAGT-3’) and XbaI (5’- T CTAGA-3’) were used to check for the in-situ DNA digestion pattern due to their inherit advantages of the short sequence of these enzymes. Both the RAPD polymorphism pattern and PFGE profile obtained showed a significant discriminatory fingerprinting among the 32 isolates under studied. A respective dendrogram was constructed from the binary data matrix obtained from the RAPD, ERIC and PFGE fingerprints to compare the diversity relationship among the 32 isolates. All the dendrograms were constructed utilizing the RAPDistance software package based on the data retrieved from the presence or absence of banding pattern. All the three molecular techniques of RAPD-, ERIC-, and PFGE genotyping showed a significant correlation whereby the first 16 and the second 16 strains of EPEC used in this study showed a closer relationship in the respective cluster groups as shown in the constructed dendrograms. From the overall results obtained both the RAPD and ERIC analysis showed greater discriminatory power compared to the other phenotypic and molecular characterization techniques used in this study. Our results demonstrate that the antimicrobial resistance,presence of resistance and virulence genes, plasmid profiling, multiplex PCR, RAPD-PCR fingerprinting, ERIC and PFGE profiling methods are useful as a suitable analysis tools for a rapid and reliable molecular typing and identification of EPEC.